Peran Instagram @cerah_indonesiaku Sebagai Media Penyampaian Pesan Perubahan Iklim kepada Generasi-Z - Tono Purwantoro; Resman Muharul Tambunan (LPPM Stikosa - AWS, 2025)
Climate change is an urgent global issue with increasingly severe impacts on the environment, economy, and public health. In the digital era, social media plays a significant role in disseminating climate-related information, especially to Generation Z, who are digital natives and highly active on platforms like Instagram. This study aims to analyze the role of the Instagram account @cerah_indonesiaku as a medium for delivering climate change messages to Generation Z in Indonesia. Using a qualitative descriptive approach and a case study method, data were collected through interviews, observations, and documentation involving the account’s managers. The findings show that Yayasan Indonesia Cerah effectively utilizes Instagram’s visual and interactive features to produce attractive, credible, and relevant climate change content. Visual elements, short videos, infographics, and contextual messages help increase engagement and encourage Generation Z to share and amplify information. This study highlights how digital communication strategies through Instagram can strengthen public awareness and promote active participation in climate change mitigation. The results contribute to understanding effective digital communication for environmental campaigns targeting youth audiences.